A Review of the Impact of Farmers-Herders Conflicts on the Socioeconomic Well-Being of Specific Local Government Areas (LGAs) in Kwara, Nigeria - Umuani Aliagan Katibi; Abd. Hakim bin Mohad@Mohamad Ramli; Ibrahim Fahad Sulaiman (Universiti Sains Islam Malaysia, 2024)
Sains Insani, Volume 9 Issue 1 Page (150-160)